Microbial network properties and functional gene diversity drive soil multifunctionality during biocrust succession - Jiang, Yawen; Zhang, Xuexia; Li, Mingjie; Yang, Jing; Zhang, Yuqing; Qin, Shugao; Feng, Wei (Frontiers in Microbiology, 2025)
IntroductionBiocrusts are critical components of desert ecosystems, performing vital functions including soil stabilization, nutrient enrichment, and regulation of carbon (C) and nitrogen (N) cycles. This study investigated the microbial mechanisms underlying biocrust-mediated soil multifunctionality (SMF) in the Mu Us Desert by comparing algal-, lichen-, and moss-dominated crusts.MethodsWe systematically sampled biocrust layers and underlying subcrust soils (0–5 cm depth), employing metagenomic sequencing and co-occurrence network analysis to characterize microbial community structures and functional properties. SMF was quantified using an integrative index based on ten parameters associated with C, N, and phosphorus (P) cycling processes.ResultsResults revealed significant variation in SMF among biocrust types, with moss crusts exhibiting the highest level, followed by lichen and algal crusts. Microbial community characteristics indicated that although lichen crusts showed the highest taxonomic diversity and network complexity, moss crusts showed a significant positive correlation with SMF. Network topological parameters, particularly network density within the biocrust layers, correlated significantly positively with SMF (p < 0.05), contrasting with the non-significant relationship observed for taxonomic diversity. Functional gene analysis revealed that the diversity of C degradation and N cycling genes exhibited a significant positive correlation with SMF.DiscussionOur findings demonstrate that biocrusts enhance SMF primarily by mediating both direct and indirect effects on N cycling functional gene diversity and microbial network complexity. This study underscores the critical role of functional gene diversity in driving biocrust-mediated ecological functions in desert ecosystems and provides a theoretical framework for developing sustainable land management and ecological restoration strategies in drylands.